Sugarcane : agricultural production, bioenergy, and ethanol / edtied by Fernando Santos, Aluízio Borém, Celso Caldas. - Santos, Fernando; Borém, Aluízio; Caldas, Celso (Academic Press is an imprint of Elsevier, 2015)
Sugarcane: Agricultural Production, Bioenergy and Ethanol explores this vital source for "green" biofuel from the breeding and care of the plant all the way through to its effective and efficient transformation into bioenergy. The book explores sugarcane's 40 year history as a fuel for cars, along with its impressive leaps in production and productivity that have created a robust global market. In addition, new prospects for the future are discussed as promising applications in agroenergy, whether for biofuels or bioelectricity, or for bagasse pellets as an alternative to firewood for home heating purposes are explored. Experts from around the world address these topics in this timely book as global warming continues to represent a major concern for both crop and green energy production.